POPULATION DIVERSITY BASED ON MORPHOMETRIC MERISTIC ENDEMIC BUTINI FISH (Glossogobius matanensis) IN LAKE TOWUTI, SOUTH SULAWESI - Jefry Jack Mamangkey; Utari Satiman; Stella Taulu (Indonesian Biodiversity Journal, 2022)
Butini fish is a resource wealth of fauna found only in the East Complex Malili Luwu, South Sulawesi. The necessary information about the morphological characters (morphometric and meristic) to determine the management of fish resources. The purpose is to assess the diversity of populations based on morphometric meristik. Sampling is based on descriptive methods and fish samples taken to determine the diversity of phenotypes based on the depth of each morphometric character. Calculating morphometric characters using the main component analysis to obtain the correlation between the character and the grouping of individuals based on morphometric characters. Calculation meristik characters include the number of fingers, the number of fins and scales, namely the number of fingers of the dorsal fin, anal fin radius, the radius of the ventral fin, pectoral fin radius, the radius of the caudal fin, scales on the rib line, scales above the rib line, scales below the ribs, scales in front of the dorsal fins, scales on the cheeks, around the body scales, scales around the tail shaft. The analysis showed that the first two principal components contained the greatest information, with a cumulative range of 80%. All the characters' morphometric first role is a major component. The character who plays the main component of the length of the head in front of the eyes, long upper jaw, lower jaw length, high cheeks, and the length of the radius of a weak base ventral fins showed great correlation to the diversity of forms. Main components analysis also showed that butini fish, at any depth, showed no grouping. This suggests that the fish species observed was one (one unit of population). In calculating the value of phenotypic diversity of each character, butini generally fish in the lake Towuti show morphometric characters with the highest diversity value and the lowest given by the total length and high under the eyes. In the calculation of the formula derived characters meristik flipper fingers that D1, V-VI. D2. I, 8-11; dan D1, V-VI, D2. I, 8-10.